Flouting Maxim Analysis in Transformer One Movie - Wirayudha, Muhammad Thoriqulhaq; Sugiharti, Dona Rahayu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This research investigates the phenomenon of flouting conversational maxims in the animated science fiction movie Transformers One, directed by Josh Cooley. Grounded in H. P. Grice’s Cooperative Principle (1975), the study identifies how characters intentionally flout the four conversational maxims of quantity, quality, relation, and manner to create implied meanings within dialogue. Using a qualitative descriptive approach, the researcher manually transcribed and analyzed dialogue from the movie, focusing on utterances that deviate from literal meaning to fulfill pragmatic functions such as sarcasm, irony, deception, and humor. A total of 25 instances of maxim flouting were found. The maxim of quality flouted (12 times), maxim of relation flouted (5 times), maxim of quantity flouted (4 times), and maxim of manner flouted (4 times). The most frequently flouted maxim was the maxim of quality. The study reveals that flouting maxim of quality often emerges in situations involving tension, rebellion, or character conflict underscoring sarcasm, exaggeration, or strategic misdirection. Characters such as Orion Pax, D-16, and B-127 flouted the maxim in the conversation not only to manipulate conversation but also to express emotional subtext, defiance, and humor. Unlike previous studies that focus on live-action dramas or comedies, this research provides insight into the pragmatic of animated science fiction dialogue. The findings suggest that flouting maxim enhances characters dialogue and supports the narrative to infer deeper meanings.